Clinical outcomes of 77 TESE treatment cycles in non-mosaic Klinefelter syndrome patients - Pedro Barbosa Soares Barros da Silva (2021)
The aim of the present work was to present the clinical outcomes of 76 azoospermic patients with non-mosaic Klinefelter syndrome, treated by testicular sperm extraction (TESE) followed by intracytoplasmic sperm injection (ICSI), using either fresh or cryopreserved testicular spermatozoa. Spermatozoa were recovered in 31/77 (40.3%) of the TESE attempts. The mean male age was 34.1 years old. In most of the cases, the testicular volume was reduced (96.1%), the levels of FSH (98.3%) and LH (94.1%) were increased, and the levels of testosterone were normal (77.6%). There were 25 ICSI treatment cycles using fresh testicular spermatozoa and 22 ICSI treatment cycles using frozen testicular spermatozoa. The rates of fertilization (63.5% vs 41.6%), implantation (37% vs 13.2%), clinical pregnancy (60.9% vs 19%), live birth delivery (52.2% vs 19%) and newborn (65.2% vs 23.8%) were higher in the group using fresh testicular spermatozoa. Chromosome analysis of the 21 newborns was normal. In conclusion, the present data adds further information regarding the recovery rate of spermatozoa after TESE and the embryological and clinical outcomes, besides reassuring the safety concerning to abnormal chromosomal transmission to the children of Klinefelter fathers.